Rapid Mobilization of an Evidence-Based Psychological Intervention for Pediatric Pain during COVID-19: The Development and Deployment of the Comfort Ability® Program Virtual Intervention (CAP-V) - Amy E. Hale; Simona Bujoreanu; Timothy W. LaVigne; Rachael Coakley (MDPI AG, 2023)
Background: The gold standard of treatment for chronic pain is a multidisciplinary approach in which psychology plays a leading role, but many children and caregivers do not gain access to this treatment. The Comfort Ability® Program (CAP) developed a CBT-oriented group intervention for adolescents and caregivers designed expressly to address access to evidence-based psychological care for pediatric chronic pain. Before the COVID-19 disruption of in-person services, the CAP workshop had been disseminated to a network of 21 children's hospitals across three countries. In March 2020, a virtual (telehealth) format was needed to ensure that children with chronic pain could continue to access this clinical service throughout the CAP Network. Methods: A model of knowledge mobilization was used to adapt the CAP workshop to a virtual format (CAP-V) and disseminate it to network sites. A pilot study assessing participant and clinician perceptions of acceptability, feasibility, and treatment satisfaction included baseline, post-sessions, and post-program questionnaires. Results: A knowledge mobilization framework informed the rapid development, refinement, and mobilization of CAP-V. Data from a pilot study demonstrated feasibility and high acceptability across participants and clinicians. Conclusions: A knowledge mobilizationframework provided a roadmap to successfully develop and deploy a virtual behavioral health intervention for adolescents with chronic pain and their caregivers during a worldwide pandemic. While CAP-V has demonstrated preliminary clinical feasibility and acceptability at the CAP hub, ongoing research is needed.